SAPHO syndrome associated with a digestive disorder in a ten-year-old girl: Diagnostic difficulties - Bérénice Dégboé; Gloria Nouhoumon; Christabelle Nguessie; Fabrice Akpadjan; Nadège Agbéssi; Christiane Koudoukpo; Zavier Zomalheto; Jean Sèhonou; Hugues Adégbidi; Félix Atadokpèdé (Our Dermatology Online, 2022)
SAPHO syndrome (acronym for synovitis, acne, pustulosis, hyperostosis, osteitis) is a rare dermato-rheumatic entity usually observed in young adults. The clinical manifestations are proteinaceous and without specificity at the origin of inflammatory diseases of the intestine. Our clinical case is that of a ten-year-old girl who presented with chronic and recurrent osteomyelitis of the pelvic limbs on a febrile background, followed by persistent and recurrent pustular lesions. During the same period, because of an acute abdominal pain syndrome accompanied by fever, a biological inflammatory syndrome, and predominantly neutrophilic hyperleukocytosis, laparotomy was performed and no lesions were found. She subsequently presented with intermittent and recurrent spasmodic abdominal pain. In view of these various symptoms, a multidisciplinary consultation concluded that the patient had SAPHO syndrome associated with a digestive disorder, possibly Crohn's disease. Our clinical case illustrates the diagnostic difficulties of SAPHO syndrome.